The Prevalence of the nematode Angiostrongylus cantonensis in the Giant African Snail (Achatina fulica), during 2012 and 2013 period in several areas of Guayaquil, Ecuador. (Revista Científica Ciencias Naturales y Ambientales, 2015)
Eight hundred and six snails have been analyzed during 2012 and 2013 in the city of Guayaquil. In terms of their prevalence for A. cantonensis, these studied samples were collected in 27 different localities (north, center and south) of the city. In 2012, 600 snails (Achatina fulica) from 7 different areas of Guayaquil were collected and dissected, 48 of which, corresponding to 8%, were positive for Angiostrongylus cantonensis. In 2013, 206 snails (A. fulica), were examined in 2 different places of Guayaquil, 8 of which, equivalent to 4%, were positive for A. cantonensis. During 2012, the results were higher at the rainy season (January to May) than in the dry season (June to December), but on 2013 fewer snails were obtained throughout the year (January to October). On March of 2012 and 2013, the northern localities: Cdla. Miraflores and Cdla. Kennedy, were positive for A. cantonensis coincidentally. This study demonstrated the dependence-existence relationship between the parasite A. cantonensis and A. fulica, in areas near the Estero Salado their populations are influenced by the rainy season (January-March).
Keywords: Achatina fulica; Angiostrongylus cantonensis; nematode; prevalence